PELATIHAN PEMBUKUAN UMKM: STUDI KASUS DI UMKM LA MALE KELURAHAN MENTAWIR PENAJAM PASER UTARA KALIMANATAN TIMUR - Ariani, Misna; Tamara, Dwinda; Yuliani, Tutik; Miswaty, Miswaty; Arrywibowo , Imam; Lestari, Winda; Khudin Anam, Sholih; Hendrawan, Yudi; Husniyah, Husniyah; Zahro, Lutfiah (Fakultas Ekonomi Universitas Balikpapan, 2024)
Documenting of financial income and expenditure transactions, in accounting must be carried out by every company, both small, medium, and large-scale companies. The success of MSMEs in general can be seen from their discipline in documenting and managing funds properly. The method of managing funds in MSMEs is to apply accounting properly. Thus, accounting allows MSMEs to obtain various financial information in running their businesses. Accounting archives must be in accordance with each transaction that occurs and based on applicable accounting standards. The problems in MSME La Male, are a special concern for the dedication to society team to conduct simple bookkeeping training. To help MSME La Male, we provide bookkeeping Training. The method used in this service is a direct discussion method using a simple bookkeeping example using excel. The results of dedication to society in MSME La Male, are that participants are happy, with a simple documenting method, because they can see directly the documenting of expenses, income, and the amount of profit